Exploring the learning environment through an organizational theory lens: A case study from nursing education - Rhoda Meyer; Elize Archer; Susan C. van Schalkwyk (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The calls for curricula review to adequately prepare nursing graduates have increased over the last decade. In response, many nursing education institutions across the world have considered ways to review and renew their curricula. Part of these renewal processes seeks to prepare nursing graduates to function within highly dynamic and challenging environments. The aim of this study was to explore the private healthcare context as a learning environment using an organizational theory lens, with a view to informing and enhancing curriculum development and implementation in nursing education. MATERIALS AND METHODS: A qualitative case study methodology within an interpretivist paradigm was used, drawing on organizational theory. The population included educators who teach undergraduate nursing students at a private higher education institution in South Africa and managers at the clinical sites where these students undertake their clinical learning. Data collection, which was undertaken over the period 2018-2020, included observations, focus group discussions, and interviews. Thematic analysis was undertaken, and a three-tiered analytical approach was followed to analyze the data. RESULTS: Four themes were identified: the learning environment as a site of tension, a site of cultural layering, a site of role complexity, and a site of hierarchy. CONCLUSION: Nursing education is dynamic, providing a range of learning experiences. An understanding of this environment from an organizational theory perspective provides some insights into potential challenges and opportunities for learning. Curriculum developers should consider ways of optimizing the opportunities so that students can be provided with learning experiences that enhance the development of the necessary competence.